PENGARUH INFLASI, JUMLAH PENDUDUK DAN PERTUMBUHANEKONOMI TERHADAPKETIMPANGAN PENDAPATAN DIPROVINSIACEH - Sri Wahyuni; Devi Andriyani (Jurnal Ekonomi Regional Unimal, 2022)
This study analyzed the effect of inflation, population, and economicgrowth on income inequality in Aceh province using data from 2005-2019. The data analysis method used was multiple linear regressionanalysis methods. The results showed that inflation had a positive andinsignificant effect on income inequality in Aceh Province. Thepopulation had a positive and significant effect on income inequality inAceh Province. Meanwhile, economic growth had a negative andinsignificant effect on income inequality in Aceh Province. The resultsof the f-test showed that inflation, population, and economic growthsignificantly influenced income inequality. Meanwhile, the results of R2showed that the ability of the independent variables to the dependentvariable was 47.55%, while the other 52.45% were influenced byvariables outside of this study.